Β-Cyclodextrin-functionalized Ti3C2Tx MXene nanohybrids as innovative signal amplifiers for the electrochemical sandwich-like immunosensing of squamous cell carcinoma antigen. Issue 10 (22nd February 2023) - Jiang, Yuling; Yang, Miao; Yu, Mingyao; Huang, Lingling; Ke, Yue; Yang, Lei
Abstract : A highly sensitive and innovative electrochemical sandwich-like immunosensing platform was designed for the detection of the squamous cell carcinoma antigen based on β-cyclodextrin-functionalized Ti3 C2 T x MXene nanohybrids as signal amplifiers. Abstract : Herein, a simple and highly sensitive electrochemical sandwich-like immunosensor for the squamous cell carcinoma antigen (SCCA) was constructed using gold nanoparticle/graphene nanosheet (Au/GN) nanohybrids as a sensing platform and β-cyclodextrin/Ti3 C2 T x MXenes (β-CD/Ti3 C2 T x ) as a signal amplifier. The good biocompatibility and large surface area as well as the high conductivity of Au/GN allow the platform to load primary antibodies (Ab1 ) and facilitate electron transport. In the case of the β-CD/Ti3 C2 T x nanohybrids, the β-CD molecule is dedicated to binding secondary antibodies (Ab2 ) through host–guest interactions, thus inducing the formation of the sandwich-like structure Ab2 -β-CD/Ti3 C2 T x /SCCA/Ab1 /Au/GN in the presence of SCCA. Interestingly, Cu 2+ can be adsorbed and self-reduced on the surface of the sandwich-like structure to form Cu 0 since Ti3 C2 T x MXenes can exhibit superior adsorption and reduction capabilities towards Cu 2+, and a prominent current signal of Cu 0 can be observed via differential pulse voltammetry. Based on this principle, an innovative signal amplification strategy has been proposed for SCCA detection, which avoids the process of labeling the probe and the specific immobilization step of catalytic components on the surface of amplification markers. After the optimization of various conditions, a wide linear range from 0.05 pg mL −1 to 20.0 ng mL −1, coupled with a low detection limit of 0.01 pg mL −1, was obtained for SCCA analysis. The proposed method for SCCA detection was also applied in real human serum samples and the observed results are satisfactory. This work opens up new pathways for constructing electrochemical sandwich-like immunosensors for SCCA and other targets.